AN APPARENT ABSENCE. AFRICANS AND AFROMESTIZOS IN LATE COLONIAL VALPARAÍSO, 1770-1820. - Contreras Segura, María Teresa (Revista de Historia Social y de las Mentalidades, 2014)
The aim of this paper is to present the  systematization of information reviewed about  people of African descent residing in late  colonial Valparaiso. Population recorded in the  Matriz El Salvador church in both 555 baptismal  items registered between 1769 and 1824, and  182 marriages performed between 1756 and  1821 in which one or both spouses had African  origins. Information showing the presence of  men, women, children and adults, slave and  free, local and foreign, that are corroborated  various mixing processes. Furthermore, data  from parish register were compared with three  censuses of the time, ie a Matrícula 1777  registration a Padrón 1787 and 1813 Census,  showing socio-ethnic diversity of the population  of Valparaíso by analyzing the appellatives  of “caste” that indicate the ‘taxonomy’ with   which priests recognize these people in their  parish books, which gave them a place in the  colonial social order conditioned by the African  ascending and miscegenation.
Keywords: Caste society; population registers; African slavery; miscegenation